Features Of Rehabilitation of Children with Childhood Cerebral Palsy - Toshmatova Zuhra Abdurahimovna (Genius Journals, 2023)
Children with cerebral palsy have weak adaptive reserves and decreased immunity. An analysis of 24 outpatient records of children with cerebral palsy showed frequent respiratory infections and chronic somatic diseases. This article deals with the problems of rehabilitation of children with cerebral palsy
Keywords: cerebral palsy; rehabilitation; complex treatment